Whole-genome survey reveals interspecific differences in genomic characteristics and evolution of Pampus fish - Zhao, Xiang; Zheng, Tianlun; Song, Na; Qu, Yinquan; Gao, Tianxiang (Frontiers in Marine Science, 2024)
Pampus belongs to the Perciformes, Stromateoidei, and Stromateidae and are widely distributed throughout the Indian Ocean and the Western Pacific. In this study, we employed next-generation sequencing to generate comprehensive genomic data for Pampus punctatissimus and Pampus echinogaster and subsequently compared the obtained genomic information with the published data of Pampus argenteus. P. echinogaster was identified to be the largest genome size (602 Mb), heterozygosity (1.38%), and repetitive sequence ratio (33.06%), while similar genome sizes between P. punctatissimus (540 Mb) and P. argenteus (550 Mb) were observed. A total of 402,921 and 628,298 SSRs were identified for P. punctatissimus and P. echinogaster, respectively. Additionally, 1,876, 638, and 394 single-copy homologous genes were identified from P. punctatissimus, P. echinogaster, and P. argenteus, respectively. The KEGG enrichment results of the unique single-copy genes to the three species were significantly different in genetic information processing, protein processing, and metabolic functions. The complete mitochondrial genomes of P. punctatissimus and P. echinogaster were successfully assembled, and the resulting phylogenetic relationships align with the currently reported taxonomic status of species in the Stromateoidei. Additionally, population size analysis using PSMC revealed that P. punctatissimus experienced one bottleneck effect, while P. echinogaster underwent two bottleneck events during the Pleistocene Glacial Epoch.